Efficacy of native grassland barriers at limiting prairie dog dispersal in Logan county, Kansas - Eddy, Zachary (Kansas State University, 2011)
Prairie dogs (Cynomys spp.) are social, ground-dwelling rodents native to North American short- and mixed-grass prairie. They are also the main prey of the Federally-endangered black-footed ferret (Mustela nigripes). At the same time, prairie dog colonization is highly opposed by most agricultural landowners. Therefore nonlethal population management techniques must be investigated. This paper presents the results of research on the effectiveness of ungrazed vegetative barriers composed of native plants at limiting prairie dog dispersal away from a ferret reintroduction site in northwest Kansas. Data was collected on barrier quality and condition as well as estimates of population densities of immigrant prairie dogs, dispersing through the vegetative barrier to reoccupy previously extirpated colonies on properties surrounding the ferret reintroduction site. Using strip transects and aboveground visual counts to estimate population densities and visual obstruction ranking techniques to sample barrier condition, statistical analysis of the data indicated that while barrier condition increased over time, it was not effective at limiting prairie dog emigration from the black-footed ferret reintroduction site.
Keywords: prairie dogs; dispersal; dispersal barrier; population management; burrow activity; colony reoccupation; Geobiology (0483); Wildlife Conservation (0284); Wildlife Management (0286)